2021
DOI: 10.25259/sni_340_2021
|View full text |Cite
|
Sign up to set email alerts
|

Surgical histopathology of a filar anomaly as an additional tethering element associated with closed spinal dysraphism of primary neurulation failure

Abstract: Background: Closed spinal dysraphism of primary neurulation failure could be associated with filar anomalies, such as filar lipoma or thickened and tight filum terminale (TFT), resulting from impaired secondary neurulation. Retained medullary cord (RMC) is a remnant of the cavitary medullary cord originating from the secondary neurulation failure. Some filar lipomas are known to contain a central canal-like ependyma-lined lumen with surrounding neuroglial tissues (E-LC w/NGT), that is, a characteristic histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“… 14 ) Recently, some studies reported that this histopathological finding was present frequently in filar and caudal lipomas, which are also believed to originate from the secondary neurulation failure. 18 , 19 ) Because central canal-like structures are not present from end to end of RMC tissue, 15 - 18 ) central canal-like structures were missing in this case whereas GFAP-positive neuroglial tissues were present. The present findings provided further evidence for the idea that RMC and filar lipomas can be considered consequences of the continuum of regression failure during secondary neurulation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“… 14 ) Recently, some studies reported that this histopathological finding was present frequently in filar and caudal lipomas, which are also believed to originate from the secondary neurulation failure. 18 , 19 ) Because central canal-like structures are not present from end to end of RMC tissue, 15 - 18 ) central canal-like structures were missing in this case whereas GFAP-positive neuroglial tissues were present. The present findings provided further evidence for the idea that RMC and filar lipomas can be considered consequences of the continuum of regression failure during secondary neurulation.…”
Section: Discussionmentioning
confidence: 76%
“…The present findings provided further evidence for the idea that RMC and filar lipomas can be considered consequences of the continuum of regression failure during secondary neurulation. 14 , 15 , 18 , 19 )…”
Section: Discussionmentioning
confidence: 99%
“…[17,18,20,21] RMC is thought to originate from the failed regression of the medullary cord, [2,17,20,24] and the characteristic histopathological feature is the presence of a central canal-like ependyma-lined lumen (CC-LELL) with surrounding neuroglial tissues (NGT), as a remnant of the medullary cord. [2,4,5,[9][10][11][12][14][15][16][17]20,23] e cyst within the RMC is histopathologically a cystic dilatation of the CC-LELL with NGT, and this pathology is called "cystic RMC. " [2][3][4]14,17,24] Although diagnostic criteria for RMC have not yet been fully established, the following three items are generally considered important: [11] (1) typical morphological features on neuroimaging and intraoperative view, [2,17,20,24] (2) the electrophysiological border between the conus and C-LS, [2,4,[9][10][11][12]17,20,21,24] and (3) CC-LELL with NGT on histopathological examination of C-LS.…”
Section: Introductionmentioning
confidence: 99%
“…As nonfunctional RMC is indistinguishable from the functional conus on neuroimaging; moreover, in the intraoperative view, detecting the presence of a nonfunctional C-LS with intraoperative neurophysiological monitoring (IONM) is mandatory for the diagnosis of RMC. [ 4 , 6 , 9 , 11 , 12 , 14 , 17 , 18 , 20 ] The characteristic histopathological feature of RMC is the predominant presence of a central canal-like ependymal-lined lumen (CC-LELL) with surrounding glial fibrillary acidic protein (GFAP)-immunopositive neuroglial tissues, as a remnant of the medullary cord. [ 4 , 6 , 9 , 11 , 12 - 17 , 18 , 21 ] Some CC-LELLs show cystic dilatation, in which case, these are referred to as “cystic RMC” or “RMC of cystic type,”[ 4 - 6 , 14 , 18 ] though Pang et al .…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 6 , 9 , 11 , 12 , 14 , 17 , 18 , 20 ] The characteristic histopathological feature of RMC is the predominant presence of a central canal-like ependymal-lined lumen (CC-LELL) with surrounding glial fibrillary acidic protein (GFAP)-immunopositive neuroglial tissues, as a remnant of the medullary cord. [ 4 , 6 , 9 , 11 , 12 - 17 , 18 , 21 ] Some CC-LELLs show cystic dilatation, in which case, these are referred to as “cystic RMC” or “RMC of cystic type,”[ 4 - 6 , 14 , 18 ] though Pang et al . [ 17 ] did not describe cystic RMCs in their initial article.…”
Section: Introductionmentioning
confidence: 99%